Body weight changes and reproductive performance of crossbred cows fed maize-lablab stover ad libitum and supplemented with graded levels of lablab hay - Mpairwe, D.R.; Sabiiti, E.N.; Umunna, N.N.; Tegegne, Azage (Tanzania Society for Animal Production, 2006)
Twenty-four multiparous Zebu × Friesian crossbred cows, were fed maize-lablab stover as basal diet and allocated to four graded levels of lablab hay (0%, 0.4%, 0.8% and 1.2% BW) treatments in a study to investigate effects of levels of lablab supplementation on body weight changes and reproductive performance. Supplementation during the first 60 days post-partum resulted in reduced weight loss (p<0.05) of the cows from -82.9 g/day to a gain of +7.1 g/day. Mean interval from calving to first post-partum ovulation improved by 19.4% but the supplemented treatments were not significantly different. Intervals from calving to first observed post-partum oestrus averaged 51 (range, 43-60) days and decreased (p<0.05) with increasing levels of lablab supplementation. Calving to conception interval was highest (95 days) for unsupplemented treatment and was reduced by supplementation although the supplemented diets were not significantly different. For optimum reproductive efficiency, it was recommended that crossbred cows fed ML stover should be supplemented with lablab hay at 0.5% BW but required additional energy supplements to meet the ME requirements for maintenance, milk production and reproductive efficiency.